2017
DOI: 10.1097/jac.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Primary Health Care Units in the Rio De Janeiro City According to the Results of PMAQ 2012

Abstract: To assess the quality of the primary health care network, the Ministry of Health created the Program for Improving Access and Quality in Primary Care (PMAQ), a national evaluation of family health teams. Thus, this study aims to present the geolocation of PMAQ 2012 quality indicators in the city of Rio de Janeiro. The PMAQ data show that, in the city of Rio de Janeiro, 65% of the teams achieved the performances “good” or “excellent,” 34.7% “regular,” and 0.3% “unsatisfactory.” The results show a clear PMAQ pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
(12 reference statements)
0
15
0
2
Order By: Relevance
“…The papers by Brazilian scholars published in this Supplement (Fausto et al, 2017;Matta-Machado et al, 2017;Mello, Tonini, Sousa da Silva, Dutt-Ross, & de Souza Velasque, 2017;Neves, Giordani, Ferla, & Hugo, 2017;Rocha et al, 2017;Tomasi et al, 2017) follow a quantitative, descriptive type of analysis based on official PMAQ data, focusing on specific clinical or epidemiological themes. They also comprise good examples of the hegemonic literature about pay for performance/PMAQ in Brazil.…”
Section: The State Of the Art Of Knowledge About Pmaq: The Relevant Gapmentioning
confidence: 99%
“…The papers by Brazilian scholars published in this Supplement (Fausto et al, 2017;Matta-Machado et al, 2017;Mello, Tonini, Sousa da Silva, Dutt-Ross, & de Souza Velasque, 2017;Neves, Giordani, Ferla, & Hugo, 2017;Rocha et al, 2017;Tomasi et al, 2017) follow a quantitative, descriptive type of analysis based on official PMAQ data, focusing on specific clinical or epidemiological themes. They also comprise good examples of the hegemonic literature about pay for performance/PMAQ in Brazil.…”
Section: The State Of the Art Of Knowledge About Pmaq: The Relevant Gapmentioning
confidence: 99%
“…The influential work on quality of care by Donabedian, which emphasizes interactions among patients, providers, and communities as fundamental to quality, is also reflected in many models of health system performance. Recent work in LMICs to assess the quality of primary care is also particularly informative; for example, a study in Brazil included an assessment of management, organization, and working conditions …”
Section: Resultsmentioning
confidence: 99%
“…The regional differences observed in this study indicate better adequacy percentages in health regions 1 (Bico do Papagaio), 2 (Médio Norte Araguaia), 4 (Cantão) and 5 (Capim Dourado), suggesting that these regions may be geographically positioned in a way that offers greater and better access to health services. Health teams that are concentrated in geographic areas that have higher numbers of primary care points were previously shown to produce the best work performance in terms of PMAQ-AB certification [ 68 ]. Studies using PMAQ-AB data have identified greater adequacy in terms of both the structure and the work process of health teams in municipalities with higher populations and higher human development indices [ 20 , 22 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%